What Line Drawings Reveal About the Visual Brain - Sayim, Bilge; Cavanagh, Patrick (Frontiers in Human Neuroscience, 2011)
Scenes in the real world carry large amounts of information about color, texture, shading, illumination, and occlusion giving rise to our perception of a rich and detailed environment. In contrast, line drawings have only a sparse subset of scene contours. Nevertheless, they also trigger vivid three-dimensional impressions despite having no equivalent in the natural world. Here, we ask why line drawings work. We see that they exploit the underlying neural codes of vision and they also show that artists’ intuitions go well beyond the understanding of vision found in current neurosciences and computer vision.